A quantitative assessment of the need for offering counseling services to medical students at the University of Zambia School of Medicine - Gretchen Slover; Kelsie Martinez; Kathrin Barnes (Health for All Nations, 2020)
Background: This research was birthed in 2017 during a trip to Lusaka, Zambia, with the purpose of offering fourth-year, medical students attending the University of Zambia, School of Medicine, lectures on psychology topics as part of their clinical studies. Students were also offered brief therapy sessions where they could process thoughts and feelings causing them internal struggles. The subject of offering counseling on a regular basis was randomly discussed with the students. From these discussions the need for this research became evident, with the intent of becoming the launching pad to brainstorm the most effective ways of developing a plan to offer counseling services for all medical students attending the University of Zambia School of Medicine. Methods: An-experimental research design, consisting of completion of a 12-item questionnaire administered by paper and pen. The inclusion criteria were the fourth year, medical students attending the University of Zambia, School of Medicine. Results: The student responses revealed that most of them had little to no experience with counseling services, but a strong desire for them. Discussion: The goal of this study was to simply establish a need for an on-campus counseling service, the need of which has been established by the very students who would benefit. With the acceptance of this need, the future plan is to explore the different ways in which this need can be fulfilled with minimal costs to the Medical School Program. Conclusion: This study is the first step towards identifying the needs of the medical students and sets the ground-work for further research into the specific areas of need and mental health challenges. More specificity in the area of demographics of students will produce a more comprehensive picture of the areas of concentration for the therapists offering services.